1998
DOI: 10.1037/1040-3590.10.2.90
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory factor analysis of the clinician-administered PTSD Scale: Evidence for the dimensionality of posttraumatic stress disorder.

Abstract: The Clinician-Administered PTSD Scale (CAPS; Blake et al, 1990) is a structured interview that assesses the 17 key symptoms of posttraumatic stress disorder (PTSD) as established in the Diagnostic and Statistical Manual of Mental Disorders (4th ed.; DSM-IV; American Psychiatric Association, 1994). CAPS data from 524 treatment-seeking male military veterans were submitted to confirmatory factor analysis to test a series of nested models reflecting alternative representations of PTSD dimensionality: (a) a 4-fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

77
1,040
9
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 713 publications
(1,131 citation statements)
references
References 35 publications
(29 reference statements)
77
1,040
9
5
Order By: Relevance
“…Results provided support for these alternative models as well, with four-factor models obtaining modestly stronger support than alternative one-or three-factor models-TLI and CFI values of .98 and .98 for the three-factor DSM-IV model, and .99 and .99 for both the King et al (1998) and Simms et al (2002) four-factor models, respectively.…”
Section: Resultsmentioning
confidence: 81%
“…Results provided support for these alternative models as well, with four-factor models obtaining modestly stronger support than alternative one-or three-factor models-TLI and CFI values of .98 and .98 for the three-factor DSM-IV model, and .99 and .99 for both the King et al (1998) and Simms et al (2002) four-factor models, respectively.…”
Section: Resultsmentioning
confidence: 81%
“…As detailed by King and colleagues (2006), many studies employing a variety of symptom questionnaires and populations support a 4-factor model (King, Leskin, King, & Weathers, 1998) that includes reexperiencing, avoidance, numbing, and hyperarousal factors (Andrews, Joseph, Shevlin, & Troop, 2006;Asmundson et al, 2000;Marshall, 2004;Palmieri & Fitzgerald, 2005). The reexperiencing and hyperarousal factors are analogous to DSM-IV symptom Clusters B and D, and the numbing and avoidance factors are drawn from Cluster C. In contrast, other studies have supported a 4-factor model identified by Simms and colleagues (2002), that includes intrusions, avoidance, dysphoria, and hyperarousal (Baschnagel, O'Connor, Colder, & Hawk, 2005;Messer, Hoge, & Castro, 2007).…”
mentioning
confidence: 89%
“…Although there is some evidence that the expression of PTSD symptoms may differ across veteran cohorts (Davidson, Kudler, Saunders, & Smith, 1990), no studies have directly examined the factorial invariance of PTSD across veteran groups. A notable point of contrast between the King et al (1998) and Simms et al (2002) studies is that although they both employed military veteran samples (Vietnam era and GulfWar I era, respectively), different PTSD symptom structures were supported for each veteran cohort. Thus, there is a need for further examination of factorial invariance of PTSD across veteran cohorts to interpret the similarities and differences in the presentation of PTSD among veterans of different wars (Rosenheck & Fontana, 1994).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…For an illustration of the most common PTSD models and their symptom mapping across factors see Table 1 (adapted from Armour et al, 2016a). Before the release of DSM-5, two four-factor models received the most empirical support: the Emotional Numbing model (King, Leskin, King, & Weathers, 1998), which divides the DSM-IV avoidance and numbing symptoms into two different factors, and the Dysphoria model (Simms, Watson, & Doebeling, 2002), which maintains the re-experiencing and avoidance factors of the Emotional Numbing model and groups some of the arousal symptoms with the numbing symptoms to create a larger, non-specific dysphoria factor separate from the remaining arousal symptoms. The five-factor Dysphoric arousal model (Elhai et al, 2011a) combines the above-mentioned models and maintains the re-experiencing, avoidance, and numbing factors of the Emotional Numbing model, but separates dysphoric arousal from anxious arousal.…”
Section: Factor Structure Of Ptsdmentioning
confidence: 99%